Factors influencing the relationship between perceptions of ecosystem services and well-being of farmers in the ore-agriculture zone, China - Wang, Fei; Shi, Xingmin; Fan, Yi (Ecological indicators, 2024)
•Farmers’ perceptions of the different ecosystem services varied.•Satisfaction with basic material needs was highest on the well-being assessment.•The overall state of ecosystem service perceptions and farmers’ well-being coupling was good.•The coupling of the dimensions of ESP and FWB was poorly coordinated from the perspective of dimensional differentiation.•Both environmental and household characteristics influenced the coupling relationship. Understanding the coupling relationship between ecosystem service perceptions (ESP) and farmers’ well-being (FWB) in the ore-agriculture zone plays an important strategic role in maintaining regional ecological security and improving the well-being of regional farmers. Based on field research, questionnaire surveys and other methods, this study took farmers around the coal mining development zone as research subjects and used a comprehensive multi-index assessment method to evaluate the level of ESP and the FWB in the research area. A coupling coordination degree model was used to analyze the coupling relationship between ESP and FWB, and the random forest model was used to explore the influencing factors of the coupling relationship between the two. The results showed: (1) The FWB index was moderate and the ESP index was low. Farmers’ perceptions of the different ecosystem services varied, with provisioning services being perceived most strongly and supporting services least strongly. Satisfaction with basic material needs was highest on the well-being assessment. (2) The overall state of ESP and FWB coupling was good, with most of them in the state of coordination improvement. From the perspective of dimensional differentiation, the coupling of the dimensions of ESP and FWB was poorly coordinated, and all of them were in the state of dysfunction regression. (3) The coupling relationship between ESP and FWB was influenced by both environmental and household characteristics, with the former having a stronger effect. The results of this study can serve as a reference for promoting the coordination of ESP and FWB in the ore-agriculture zone, and ultimately realize the sustainable development of ecology and human in the ore-agriculture zone.